Gleaning Fisheries as Context for Culturally Relevant Contents for Science Teaching - Garlan, Michael (Journal of Interdisciplinary Perspectives, 2025)
This exploratory-sequential study investigates the integration of indigenous knowledge from a Philippine gleaning fishery into science education to contextualize curriculum content and enhance socio- cultural relevance and environmental consciousness. Thematic analysis revealed five key domains of indigenous science: fisheries management, religion, health, conservation biology, and earth science, each offering connections to socio-scientific and environmental issues. A prototype lesson plan was developed based on these themes and underwent pilot testing with 60 participants (30 teachers and 30 students) from a coastal community engaged in gleaning activities. Results showed a moderate acceptance among students (M = 2.99, SD = 0.486) and a high level of acceptance among teachers (M = 3.95, SD = 0.486), as measured using a 4-point Likert scale. The findings underscore the pedagogical value of indigenous knowledge in fostering scientific thinking, environmental stewardship, and culturally responsive teaching. Embedding cultural practices into science instruction empowers educators to create inclusive, meaningful, and contextually grounded learning environments.